2020
DOI: 10.20473/ijar.v2i12020.8-12
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Basic Life Support (BLS) Training in The Knowledge and Skill Level of Community in Sidodadi Village, Lawang, Indonesia

Abstract: Introduction: About 300.000 -350.000 Indonesian people suffer from cardiac arrest each year. Basic Life Support (BLS) is the first immediate response needed by cardiac arrest people, especially the out of hospital cardiac arrest (OHCA) patient. BLS that given from public to OHCA could increase the survival rate up to 2 -3x higher. Unfortunately, the Indonesian still did not know what is cardiac arrest, how to recognize it, and how to do BLS. Objective: The objective of this study was to identify the effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 5 publications
0
3
0
7
Order By: Relevance
“…We found that there was a significant increase in the level of knowledge of the trainers after the provision of material about BLS. Stella et al, states that the provision of knowledge and skills has been proven to be an effective way to increase the knowledge level of coaches about BLS [25]. Not only knowledge, but it is also required for every trainer to have the skills and trainer's certificate, especially related to injury management, including BLS [13,21].…”
Section: Discussionmentioning
confidence: 99%
“…We found that there was a significant increase in the level of knowledge of the trainers after the provision of material about BLS. Stella et al, states that the provision of knowledge and skills has been proven to be an effective way to increase the knowledge level of coaches about BLS [25]. Not only knowledge, but it is also required for every trainer to have the skills and trainer's certificate, especially related to injury management, including BLS [13,21].…”
Section: Discussionmentioning
confidence: 99%
“…BLS yang diberikan oleh awam pada OHCA mampu meningkatkan survival rate sebanyak 2 hingga 3x lipat. Sayangnya, masyarakat Indonesia masih banyak yang belum mengetahui apa itu henti jantung, bagaimana cara mengenalinya, dan bagaimana cara melakukan BLS (Stella et al, 2020). Salah satu masyarakat yang masih belum mengetahui hal tersebut adalah anggota Karang Taruna Trisula di Desa Sukorejo, Kecamatan Karangbinangun, Lamongan.…”
Section: Problemunclassified
“…Dimana tingkat pengetahuan responden memiliki hubungan salah satunya dengan keikutsertaan dalam pelatihan BLS (Hidayati, 2020;Muthmainnah, 2019). Berdasarkan hal tersebut, disarankan tenaga kesehatan yang memiliki kemampuan dalam pemberian BLS hendaknya dapat mengajarkan masyarakat umum (Hidayati, 2020;Stella et al, 2020;ZA, 2014), salah satunya ke karang taruna.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…About 99% of people who have joined BLS training have a significant increase in knowledge and skills. These trained people have the willingness to be a bystander for cardiac arrest people near them (Stella et al, 2020). Comprehensive interventions are needed to reduce exposure and health risks, including training, increased labeling, measures to reduce cost barriers for implementing safe behavior, promotion of control measures, and support for integrated pest management (Lekei et al, 2014).…”
Section: Knowledge Of Emergency Managementmentioning
confidence: 99%